Atomistic investigation on the effect of temperature on mechanical properties of diffusion-welded Aluminium-Nickel - Zaenudin, Mohamad; Abdulrazaq, Mohammed N.; Al-Zubaidi, Salah S. (International Journal of Integrated Engineering, 2020)
Atomistic investigation of diffusion welding between Aluminium and Nickel has been investigated, by means of Molecular Dynamics (MD) simulation. This study focuses on examining the effect of temperature on diffusion welding between Al-Ni for which it is still lacking. Employing several different temperatures, this study aims to examine the influence of temperature on the mechanical properties of diffusion-welded Al-Ni. The results have shown that the structural evolution significantly affected by the temperature. Better bonding structure is achieved as the temperature is increased which indicated by the wider interfacial region thickness on concentration profiles. However, as the temperature is increased lower ultimate tensile strength is obtained. Therefore, precisely estimates the temperature for particular materials in diffusion welding is a critical point. In this study, the optimum condition that fitsA on the diffusion welding process is when the temperature set on 500 K.